A LEARNING MODEL DEVELOPMENT OF CRITICAL READING COMPREHENSION THROUGH RECIPROCAL TEACHING - Budiasih Budiasih; Fitri Ana Ika Dewi (Leksema: Jurnal Bahasa dan Sastra, 2019)
This research aims at designing a learning model of critical reading based on Reciprocal Teaching. This research is a Research and Development (R&D) which applies the theory of Borg & Gall (2007). The subject is the second semester students that consist of 60 students in the academic year of 2017-2018. Data are obtained form interviews of lecturers and students, observation during implementation, and validation notes. The expert judgment was applied to validate the design of the learning model. The final product of the research is a learning model of critical reading by applying the strategy of Reciprocal Teaching consisted of four activities namely summarizing, questioning, clarifying, and predicting which is extended into six activities namely, predicting, questioning, clarifying, self-monitoring, summarizing, and evaluating. The model is considered to be supportive to the critical reading instructional since the students can complete the written tasks successfully.